PENGARUH PEMBERIAN UREA, TSP, KCl DAN PUPUK ORGANIK CAIR (POC) KULIT PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH KERITING (Capsicum annum L.) - adrian, Edo; Yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research to determine the interaction of inorganic fertilizer (Urea, TSP, KCl)and banana peelliquid organic fertilizer (POC) to find the best results on the growth and yield of red pepper (Capsicum annuum L.).This study was conducted for four months (March-June, 2016), the Experimental Station, Faculty of Agriculture, University of Riau Pekanbaru,using a completely randomized design (CRD) factorial,consists of two factors and three replications.The results were analyzed by analysis of variance and Duncan's New Multiple Range Test (DNMRT) at 5%. The study suggest thatthe interaction of inorganic fertilizer and banana peel liquid organic fertilizer (POC) did not increasehe stealDiameter, flowering age after transplanting, fruit length, and Shoot to Root Ratiobut give increaseof plant height, diameter of the fruit, yield, number of fruits, and fresh fruit weight.Urea of 1.25, 2.59 TSP, KCl 2 g / 10 kg of soil and banana peel liquid organic fertilizer (POC) 300 ml / literprovide improvement on chili the growth and yield..Â Keywords: Chili Plant, Inorganic Fertilizer, Fertilizer POC Banana Peel and Plant Growth.